2021
DOI: 10.3390/pr9020336
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Benzene-Cyclohexane Azeotropes Via Extractive Distillation Using Deep Eutectic Solvents as Entrainers

Abstract: The separation of benzene and cyclohexane azeotrope is one of the most challenging processes in the petrochemical industry. In this paper, deep eutectic solvents (DES) were used as solvents for the separation of benzene and cyclohexane. DES1 (1:2 mix of tetrabutylammonium bromide (TBAB) and levulinic acid (LA)), DES2 (1:2 mix of TBAB and ethylene glycol (EG)) and DES3 (1:2 mix of ChCl (choline chloride) and LA) were used as entrainers, and vapor-liquid equilibrium (VLE) measurements at atmospheric pressure rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The peak at 1106 cm –1 belongs to the −COH stretching vibration. 33 When the ternary DES is formed, blue-shifts are observed for the stretching vibration peak of −OH in ChCl and the stretching vibration and bending vibration of −NH 2 in U. At the same time, the intensity of the −OH in EG is enhanced, which indicated that they are all involved in the formation of the large number of hydrogen bonds (N–H···Cl, O–H···O, O–H···Cl, etc.)…”
Section: Resultsmentioning
confidence: 98%
“…The peak at 1106 cm –1 belongs to the −COH stretching vibration. 33 When the ternary DES is formed, blue-shifts are observed for the stretching vibration peak of −OH in ChCl and the stretching vibration and bending vibration of −NH 2 in U. At the same time, the intensity of the −OH in EG is enhanced, which indicated that they are all involved in the formation of the large number of hydrogen bonds (N–H···Cl, O–H···O, O–H···Cl, etc.)…”
Section: Resultsmentioning
confidence: 98%
“…For levulinic acid, the broad peak in the range of 3000–3500 cm –1 corresponds to the stretching vibration of hydroxyl (−OH), while the peak at 1699 cm –1 represents the stretching vibration of carbonyl (−CO) . For TBPB, the peaks at 2873–2960 cm –1 represent the methylene (−CH 2 ) and methyl (−CH 3 ) group asymmetric and symmetric stretching vibrations .…”
Section: Resultsmentioning
confidence: 99%
“…For levulinic acid, the broad peak in the range of 3000−3500 cm −1 corresponds to the stretching vibration of hydroxyl (−OH), while the peak at 1699 cm −1 represents the stretching vibration of carbonyl (−CO). 45 For TBPB, the peaks at 2873−2960 cm −1 represent the methylene (−CH 2 ) and methyl (−CH 3 ) group asymmetric and symmetric stretching vibrations. 39 After mixing levulinic acid and TBPB, their FTIR spectra clearly show that the band of the hydroxyl (−OH) group of levulinic acid narrows and shifts to a lower wavenumber (known as a red shift), with increasing the TBPB content from TBPB/LA (1:6) to TBPB/LA (1:2).…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results are provided in Table 7. In the systems containing DES(TBAB:LA) (1:2) and DES(ChCl:LA) (1:2) [31], the prediction is satisfactory as the coefficient of determination is >0.99 assessed from all the three models. In the system containing DES(TBAB:LA) (1:2), the prediction is not satisfactory since the coefficient of determination is <0.99 using the three models.…”
Section: Vle Data Correlationmentioning
confidence: 96%